2013
DOI: 10.1002/pbc.24913
|View full text |Cite
|
Sign up to set email alerts
|

Use of allopurinol in children with acute lymphoblastic leukemia to reduce skewed thiopurine metabolism

Abstract: Mercaptopurine (6-MP), a critical component of acute lymphoblastic leukemia (ALL) therapy, is metabolized to 6-thioguanine (6-TGN) which is responsible for its anti-leukemic effect, and to 6-methylmercaptopurine nucleotides (6-MMPN/6-MMP) which can be hepatotoxic. Some patients preferentially metabolize 6-MP to 6-MMPN which may increase the risk of liver injury, reduce serum levels of 6-TGN and potentially increase the risk of relapse. The addition of allopurinol to oral 6-MP has been shown to optimize metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…For example, genotypic polymorphisms in the enzyme thiopurine methyltransferase are associated with increased myelosuppression and other toxicities, whereas other polymorphisms confer a “hypermetabolizer” state, with decreased levels of the active metabolite. 19 Understanding these differences in metabolism is particularly important because studies have shown that the degree of myelosuppression correlates with relapse risk. 20,21 Accordingly, many protocols include guidelines for dose adjustments to assist in achieving the goal of balancing the risks of inadequate myelosuppression with the risks of severe pancytopenia (infection, bleeding, and so forth).…”
Section: Treatment Of Newly Diagnosed Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…For example, genotypic polymorphisms in the enzyme thiopurine methyltransferase are associated with increased myelosuppression and other toxicities, whereas other polymorphisms confer a “hypermetabolizer” state, with decreased levels of the active metabolite. 19 Understanding these differences in metabolism is particularly important because studies have shown that the degree of myelosuppression correlates with relapse risk. 20,21 Accordingly, many protocols include guidelines for dose adjustments to assist in achieving the goal of balancing the risks of inadequate myelosuppression with the risks of severe pancytopenia (infection, bleeding, and so forth).…”
Section: Treatment Of Newly Diagnosed Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…As dose increments of 6MP increase the methylated metabolites and their associated toxicities far more than Ery-6TGN, several alternative treatment strategies have been efficacious in improving the 6TGN/MeMP ratio, including coadministration of allopurinol70,71,90 and splitting the daily 6MP dose in a morning and an evening dose,91,92 but it remains to be determined whether such approaches increase DNA-TG levels, ease 6MP dose adjustments to obtain target WBC/absolute neutrophil counts (ANC) levels, or reduce relapse rates of childhood ALL.…”
Section: Mp and Mtx Pharmacokinetics And Pharmacodynamicsmentioning
confidence: 99%
“…The VDLD therapeutic regime that has been used clinically is the first-line approach for treatment of A-BLL. However, recent research has indicated an increase in the rate of resistance to chemotherapeutic drugs; in addition, these drugs impart severe toxic and side effects, thereby restricting the clinical use of this therapeutic regime (Brackett et al, 2014;Melachuri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%